ALBUMIN AND TOTAL PROTEIN LEVELS IN DOGS WITH ATOPIC DERMATITIS AFTER TREATMENT WITH COCONUT OIL AND DIPHENHYDRAMINE - Serli Rohayu; I Nyoman Suartha; Putu Devi Jayanti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Atopic dermatitis is a chronic inflammatory skin disease in dogs that is often characterized by pruritus, damage to the skin barrier, and impaired protein metabolism. This study aimed to determine the effect of the combination of coconut oil and diphenhydramine on albumin and total protein levels in dogs with atopic dermatitis. A total of 15 dogs were diagnosed with atopic dermatitis. This study used a pre-test and post-test design with treatment for 28 days in the form of giving coconut oil once a day and diphenhydramine twice a day. Blood samples were taken before and after treatment to analyze albumin and total protein levels using automated biochemical tools. The results showed an increase in albumin levels from 2.31 g/dL on day 0 to 2.82 g/dL on day 28 (p<000) and an increase in total protein from 6.17 g/dL on day 0 to 7.24 g/dL on day 28 (p<001), which statistically showed a statistically significant effect. It can be concluded the combination therapy of coconut oil and diphenhydramine has a significant effect on increasing albumin and total protein levels in dogs with atopic dermatitis. It is recommended that follow-up studies be conducted with the control group and that sampling frequency be conducted once a week to determine the specific contribution of each therapy.